Pengelolaan Meta Business Suite sebagai Media Komunikasi Digital Hotel Novotel Jakarta Gajah Mada - Andien Putri Aliffia Saputra; Leonard Dharmawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study analyzes the management of Meta Business Suite (MBS) and the use of the Koddie platform as digital communication media at Hotel Novotel Jakarta Gajah Mada. Using a descriptive qualitative case study approach, this research examines managerial processes based on the POAE framework through data triangulation. The findings reveal that MBS functions as a daily operational hub integrated with Koddie for budget management and cross-channel media placement. Key issues identified include a significant decline in Instagram organic engagement by 95.8% and the dominance of bookings through Online Travel Agents (OTA) rather than the official hotel website. While in-house management provides advantages in message control and coordination flexibility, improvements are needed in visual content strategy and website user journey to enhance audience engagement and conversion in a competitive digital landscape.